1967
DOI: 10.1111/j.1365-2621.1967.tb01303.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cooking on Chlorinated Hydrocarbon Pesticide Residues in Chicken Tissues.

Abstract: SUMMARY— DDT and lindane were fed separately and in combination at levels of 0.2 and 2.0 ppm to chickens during a growing period of 9 weeks. Pesticides incorporated into the tissues were reduced considerably when the birds were cooked by baking or frying. DDT, DDE, and Kelthane were present in the control and cooked carcasses, but DDD was found only in the cooked birds. A relationship between the two pesticides in which lindane enhanced the retention of DDT in the tissues appeared possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1969
1969
1980
1980

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…Drip from samples cooked by baking had, in general, lower levels (P < 0.01) of dieldrin than samples cooked by frying, thereby showing an inverse relationship with the dieldrin content of the cooked bacon. These data support the conclusions of other investigations showing that pesticide residue levels can be reduced by cooking (Ritchey et al, 1967(Ritchey et al, , 1969Liska et al, 1967;McCaskey et al, 1968).…”
Section: Resultssupporting
confidence: 91%
“…Drip from samples cooked by baking had, in general, lower levels (P < 0.01) of dieldrin than samples cooked by frying, thereby showing an inverse relationship with the dieldrin content of the cooked bacon. These data support the conclusions of other investigations showing that pesticide residue levels can be reduced by cooking (Ritchey et al, 1967(Ritchey et al, , 1969Liska et al, 1967;McCaskey et al, 1968).…”
Section: Resultssupporting
confidence: 91%
“…Rendering of the PCB's with the fat appears to be the major mode of removal since PCB levels expressed on a fat basis (Tables 2 and 4) were similar. Ritchey et al (1967Ritchey et al ( , 1969 had previously indicated that rendering during cooking significantly reduced chlorinated hydrocarbon pesticides in chicken.…”
Section: Resultsmentioning
confidence: 98%
“…Cooking results in substantial losses of organochlorine pesticides in chicken (Mc-Caskey et al, 1968;Morgan et al, 1972;Ritchey et al, 1967Ritchey et al, , 1969. Nevertheless, Smith et al (1973) reported that cooking produced very little loss of PCB's from chinook and coho salmon.…”
Section: Introductionmentioning
confidence: 91%
“…Fifteen White Leghorn hens, approximately 9 months of age, were fed a standard cage layer ration for 5 weeks which was contaminated with 0, 30, 45, 60, and 90 ppm FireMaster FF-I (three hens/feeding level). At the end of 5 weeks the first three groups (0, 30, and 45 ppm levels) were slaughtered.…”
Section: Pressure Cookingmentioning
confidence: 99%
“…Condensation has shown to be effective in the reduction of telodrin in milk (2), freeze-drying significantly reduced lindane, dieldrin, p,p'-DDT, and o,p'-DDT-DDD from whole eggs (3), heating skimmed milk decreased PCB residues (4), and spray-drying promoted losses of chlorinated hydrocarbon pesticides (5,6). Cooking has reduced these lipophylic compounds from such products as poultry (7)(8)(9)(10)(11), sausage patties (12), bacon (13), pork loins (14), pork muscles (15) and beef loaves with texturized soy (16). Most of the losses were attributed to fat rendering or leaching out during cooking-the more severe the rendering the greater the loss.…”
Section: Introductionmentioning
confidence: 99%